(untitled) (Jurnal Teknologi (Sciences & Engineering), 2023)
This research aims to utilize marble industrial waste which is not utilized optimally and reduce air pollution as a result of cement production in cement industrial factories which produce a lot of CO2 emissions. The results of this research indicate that the use of 25 % Graphite Carbon Marble Particle Powder, to replace 25 % of the cement volume in making concrete with quality plans K-250 or fc’ 20,75 MPa. The results obtained are higher concrete quality than the quality of each concrete planned for the DCT type = 22,39 MPa > 20,75 MPa, DCL type = 22,76 MPa > 20,75 MPa, WCT type = 22,14 MPa > 20,75 MPa and WCL type = 22,89 MPa > 20,75 MPa. The compressive strength testing process is caried out based on ASTM C 39/C 39M – 05. Meanwhile for workability based on the results of the slump test, a slump value of 12 cm is obtained with the testing process referring to SNI 1972:2008 and ASTM C143/C143M-12.